BİR EMME MANİFOLDUNDAKİ AKIŞIN SAYISAL OLARAK İNCELENMESİ - ÖZTEKİN, FERHAT (Fırat Üniveristesi, 2019)
Bu çalışmada;üçfarklıemme manifoldusolidworksporgramındatasarlanarak,bumanifoldlarınhız parametreleri,HesaplamalıAkışkanlarDinamiği(HAD) analiziile sayısalolarak incelenmiş veemme manifoldu sayısalmodelitasarımıiçindört silindirlibir aracınmanifold modelikullanılmıştır. Analizlerde akışkanolarakhavakullanılmıştır. Emmemanifolduna farklı hızlar verilerekemme kanallarınıngirişaçılarınınetkilerive çıkış debileri incelenmiştir. Sayısal çözümlemede ANSYSFluentyazılımı emme manifolduiç akışınıanalizetmekiçinkullanılmıştır.Analiz sonuçları doğrultusundaemmemanifoldu için eniyiiç akış koşullarının belirlenmesi amaçlanmıştır. Literatürdeki tasarım ile karşılaştırılarak sonuçlar değerlendirilmiştir. Emme kanallarının çıkış hızlarının silindir içerisine eşit olarak dağılması için en uygun tasarım belirlenmiştir.

In this study; three different intake manifolds were designed in solidworks program and the velocity parameters of these manifolds were analyzed numerically by Computational Fluid Dynamics (HAD) analysis and manifold model of a four cylinder vehicle was used for designing the intake manifold numerical model. Air was used as fluid in the analyzes. The effects of inlet angles of inlet ducts and outlet flow rates were examined by giving different speeds to intake manifold. In numerical analysis, ANSYS Fluent software was used to analyze the intake manifold internal flow. According to the results of the analysis, it was aimed to determine the best internal flow conditions for the intake manifold. The results were compared with the design in the literature. The most suitable design has been determined for the distribution of the exit velocity of the suction channels evenly into the cylinder. Keywords: Intake Manifold, Computational Fluid Dynamics (HAD), ANSYS Fluent.
A numerical analysis of flow in an intake manifold
Keywords: Makine Mühendisliği